Operational Efficiency Criteria of School - Visockaitė, Audra; Čižikienė, Janina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article analyses the problem of school work efficiency. The research of efficiency is provided with evaluation criteria offered by various authors, the possibilities of their application in Lithuanian schools are being analysed in the aspect of work efficiency. Modern comprehension of efficient school in Lithuania should be clear and understandable for all groups of interest: students, teachers, parents, school leaders and founders, education institutions and the society. During the continuous changes and reforms, school education in Lithuania is often based on the traditional model of institutional education, which is based on the principles of discipline, obedience and competitiveness. However, in the modern stage, characteristics of analytic thinking, creativity are appreciated. Therefore, emerges a need to change the attitude to requirements for efficient school, evaluate the work fields of school as an organization by improving them with regard to the needs of ever-changing society. In the end of the article, conclusions are presented which distinguish the peculiarities of school work efficiency.